Evidence for an evolutionarily conserved interaction between cell wall biosynthesis and flowering in maize and sorghum - Vermerris, Wilfred (BioMed Central, 2002)
BACKGROUND: Factors that affect flowering vary among different plant species, and in the grasses in particular the exact mechanism behind this transition is not fully understood. The brown midrib (bm) mutants of maize (Zea mays L.), which have altered cell wall composition, have different flowering dynamics compared to their wild-type counterparts. This is indicative of a link between cell wall biogenesis and flowering. In order to test whether this relationship also exists in other grasses, the flowering dynamics in sorghum (Sorghum bicolor (L.) Moench) were investigated. Sorghum is evolutionarily closely related to maize, and a set of brown midrib (bmr) mutants similar to the maize bm mutants is available, making sorghum a suitable choice for study in this context. RESULTS: We compared the flowering time (time to half-bloom) of several different bmr sorghum lines and their wild-type counterparts. This revealed that the relationship between cell wall composition and flowering was conserved in sorghum. Specifically, the mutant bmr7 flowered significantly earlier than the corresponding wild-type control, whereas the mutants bmr2, bmr4, bmr6, bmr12, and bmr19 flowered later than their wild-type controls. CONCLUSION: The change in flowering dynamics in several of the brown midrib sorghum lines provides evidence for an evolutionarily conserved mechanism that links cell wall biosynthesis to flowering dynamics. The availability of the sorghum bmr mutants expands the germplasm available to investigate this relationship in further detail.